Friction based additive manufacturing technologies : principles for building in solid state, benefits, limitations, and applications - Rathee, Sandeep; Srivastava, Manu; Maheshwari, Sachin; Kundra, T. K.; Siddiquee, Arshad Noor (CRC Press, 2018)
"Friction additive manufacturing is a term used for friction based solid state welding processes in conjugation with additive manufacturing, to produce components with superior structural and mechanical properties. This is a novel manufacturing technology of developing high structural performance components. It utilizes the principle of layer by layer additive manufacturing and is a major breakthrough in metal additive manufacturing. The book is a compilation of friction based solid state processes and additive manufacturing principles, and will cover the methodological principles, benefits, limitations, and applications of additive manufacturing and friction stir welding processes."--Provided by publisher.